2016
DOI: 10.1186/s12929-016-0273-0
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Newcastle disease virus expressing P53 demonstrates promising antitumor efficiency in hepatoma model

Abstract: BackgroundNumerous studies have demonstrated that the NDV-mediated gene therapy is a promising new approach for treatment of cancers. P53 plays a vital role in tumor suppression and surveillance. Therefore, we hypothesize that a recombinant NDV expressing P53 would be an ideal agent for the hepatoma therapy.ResultsIn the essay, the human P53 gene was incorporated into the genome of a lentogenic strain (named rNDV-P53), which did not affect viral replication kinetics and magnitude in HepG2 cells. Compared to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 42 publications
0
20
0
1
Order By: Relevance
“…The current trend is to use recombinant strains with decreased pathogenicity and improved antitumor effect [ 21 26 ]. However, naturally occurring oncolytic NDV strains are also observed.…”
Section: Introductionmentioning
confidence: 99%
“…The current trend is to use recombinant strains with decreased pathogenicity and improved antitumor effect [ 21 26 ]. However, naturally occurring oncolytic NDV strains are also observed.…”
Section: Introductionmentioning
confidence: 99%
“…WT p53 transgenes also increased cytotoxicity of two other OVs, VSV and NDV 48, 54, 61, 67. In our recent study, VSV-p53 showed enhanced killing of the pancreatic cancer cell line SUIT2 compared with VSV not expressing p53 when these viruses were tested at a low MOI 67 .…”
Section: Main Textmentioning
confidence: 76%
“…Other OVs armed with a p53 transgene were demonstrated to be safe in animals, including Newcastle disease virus (NDV; a paramyxovirus) 61 and various recombinant VSVs 62 . Toxicity studies in mice showed that after 10 systemic injections of rNDV-p53 (1 × 10 7 PFU each), the serum from mice showed no changes in serum creatinine, aspartate transaminases, alanine transaminases, or blood urea nitrogen levels, supporting the safety of that virus 61 .…”
Section: Main Textmentioning
confidence: 99%
“…NDV has been used to treat neuroblastoma, melanoma, and other malignancies. Previous studies have reported that the tumor volume is substantially decreased after NDV infection …”
Section: Discussionmentioning
confidence: 95%